2018
DOI: 10.1038/s41598-018-30752-8
|View full text |Cite
|
Sign up to set email alerts
|

The small heat shock protein HSPB1 protects mice from sepsis

Abstract: In vitro studies have implicated the small heat shock protein HSPB1 in a range of physiological functions. However, its in vivo relevance is unclear as the phenotype of unstressed HSPB1−/− mice is unremarkable. To determine the impact of HSPB1 in injury, HSPB1−/− and wild type (WT) mice were subjected to cecal ligation and puncture, a model of polymicrobial sepsis. Ten-day mortality was significantly higher in HSPB1−/− mice following the onset of sepsis (65% vs. 35%). Ex vivo mechanical testing revealed that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…An earlier report using HeLa cells showed that HSPB1 is associated with the expression of proinflammatory factors and involved in the IL-1 and TNFinduced signaling [72]. In C6 glioma cells, the chaperone activity of HSPB1 contributed to the production of the pro-inflammatory cytokine, IL-6, whereas T cells from HSPB1 −/− mice exhibited reduced secretion of TNF and IL-2 [74,75]. Recombinant HSPB1 treatment also resulted in enhanced pro-inflammatory cytokine expression in vitro [18,76,77].…”
Section: Discussionmentioning
confidence: 99%
“…An earlier report using HeLa cells showed that HSPB1 is associated with the expression of proinflammatory factors and involved in the IL-1 and TNFinduced signaling [72]. In C6 glioma cells, the chaperone activity of HSPB1 contributed to the production of the pro-inflammatory cytokine, IL-6, whereas T cells from HSPB1 −/− mice exhibited reduced secretion of TNF and IL-2 [74,75]. Recombinant HSPB1 treatment also resulted in enhanced pro-inflammatory cytokine expression in vitro [18,76,77].…”
Section: Discussionmentioning
confidence: 99%
“…This limited protection could be explained by the contribution of different factors, including other isoforms of Hsp70, Hsp40, Hsp27, and Hsp90, which share overlapping function at different levels. In addition to the induction of atopic dermatitis, Hsp27 is known to contribute in the production of proinflammatory cytokines (19,32,33). Pezzulo et al (34) have demonstrated the critical role of Hsp90 in the induction of goblet cell hyperplasia and mucus production.…”
Section: Hsp70 Induces Th2 Responses and Airway Inflammationmentioning
confidence: 99%
“…The HSPB1 gene expresses HSPB1, heat shock protein beta-1 protein (also known as Hsp27, heat shock protein 27). This protein is a member of the heat shock protein family, which helps to protect cells under adverse conditions such as infection, inflammation, exposure to toxins, elevated temperature, injury, and disease [19]. HSPB1 acts as a potent inhibitor of apoptosis signaling [20].…”
Section: Resultsmentioning
confidence: 99%